Operationalizing Zakat as A Social Welfare Instrument: A Normative–Sociological Analysis of Pancasila Values in Indonesia - Galih Orlando; Muhamad Hasan Sebyar; M. Iqbal Irham; Asmuni Asmuni (Madania: Jurnal Kajian Keislaman, 2025)
Zakat, as a central pillar of Islamic socio-economic justice, serves not only as a religious obligation but also as a mechanism for redistributing wealth and promoting social welfare. In Indonesia, where Pancasila functions as the national ideology and moral compass of development, the implementation of zakat reflects a convergence between faith-based ethics and state-based welfare ideals. This study examines zakat as a social welfare instrument that operationalizes the philosophical values of Pancasila within Indonesia’s pluralistic welfare system. While existing studies largely focus on the economic or administrative dimensions of zakat, this research contributes by conceptualizing zakat as an ideological and ethical mechanism that bridges Islamic moral economy and state-based welfare principles. Employing a qualitative normative–sociological approach, the study analyzes Islamic legal sources, national zakat regulations, particularly Law No. 23 of 2011 on Zakat Management, and institutional practices of the National Zakat Agency (BAZNAS) through document analysis and institutional interpretation. The findings demonstrate that zakat implementation in Indonesia embodies Pancasila values through three integrative dimensions: spiritual justice grounded in belief in One Almighty God, social solidarity reflecting humanitarian and communal ethics, and distributive justice aligned with the fifth principle of Pancasila—social justice for all Indonesian people. This study argues that the zakat–Pancasila nexus offers an inclusive and ethically grounded welfare model, providing both theoretical insights for Islamic legal studies and practical implications for public welfare governance in Indonesia. Zakat, sebagai salah satu pilar utama keadilan sosial-ekonomi Islam, tidak hanya berfungsi sebagai kewajiban keagamaan, tetapi juga sebagai mekanisme redistribusi kekayaan dan peningkatan kesejahteraan sosial. Di Indonesia, di mana Pancasila berfungsi sebagai ideologi nasional sekaligus pedoman moral pembangunan, pelaksanaan zakat mencerminkan titik temu antara etika berbasis keagamaan dan cita-cita kesejahteraan yang dibangun oleh negara. Penelitian ini mengkaji zakat sebagai instrumen kesejahteraan sosial yang mengoperasionalkan nilai-nilai filosofis Pancasila dalam sistem kesejahteraan Indonesia yang bersifat pluralistik. Sementara penelitian-penelitian sebelumnya umumnya menitikberatkan pada dimensi ekonomi atau administratif zakat, studi ini memberikan kontribusi dengan memposisikan zakat sebagai mekanisme ideologis dan etis yang menjembatani ekonomi moral Islam dengan prinsip-prinsip kesejahteraan berbasis negara. Penelitian ini menggunakan pendekatan kualitatif normatif–sosiologis dengan menganalisis sumber-sumber hukum Islam, regulasi nasional tentang zakat—khususnya Undang-Undang Nomor 23 Tahun 2011 tentang Pengelolaan Zakat, serta praktik kelembagaan Badan Amil Zakat Nasional (BAZNAS) melalui analisis dokumen dan interpretasi institusional. Hasil penelitian menunjukkan bahwa implementasi zakat di Indonesia merefleksikan nilai-nilai Pancasila melalui tiga dimensi integratif, yaitu: keadilan spiritual yang berlandaskan pada Ketuhanan Yang Maha Esa, solidaritas sosial yang mencerminkan nilai-nilai kemanusiaan dan kebersamaan, serta keadilan distributif yang selaras dengan sila kelima Pancasila, yakni keadilan sosial bagi seluruh rakyat Indonesia. Penelitian ini menegaskan bahwa relasi zakat dan Pancasila menawarkan model kesejahteraan yang inklusif dan berlandaskan etika, sekaligus memberikan kontribusi teoretis bagi kajian hukum Islam serta implikasi praktis bagi tata kelola kesejahteraan publik di Indonesia